Toleransi beragama sebagai dasar keharmonisan di perguruan tinggi - Safitri, Noveli Dian (Maliki Interdisciplinary Journal, 2026)
Indonesia’s national identity functions as an important unifying tool in facing the diversity of ethnicities, religions, and cultures. As a country with great diversity, Indonesia strongly needs an attitude of mutual respect in order to create a harmonious life. Tolerance helps people accept and respect differences without looking down on other groups. With tolerance, people can live side by side peacefully and maintain national unity. In everyday life, tolerance can be practiced through simple actions, such as respecting other people’s opinions, not forcing one’s will on others, and respecting everyone’s right to practice their own beliefs. This attitude is important to apply in all environments, including educational institutions. Universities are places with a high level of diversity because they bring together students from various regions and backgrounds. Student involvement in campus organizations also has a positive influence on the development of tolerant attitudes.